Breast Cancer: Preparing for Surgery - Martha C. Monroe; Barbara F. Shea (EDIS)
Once you and your doctor schedule your breast cancer surgery, you may have additional questions about how you can prepare for your operation. This revised 5-page fact sheet provides information to help you get ready for breast cancer surgery through a brief overview of common surgical options, medical appointments, social support systems, and standard surgical procedures, as well as reactions and memories of women who have gone through this experience. Written by Martha C. Monroe and Barbara F. Shea, and published by the UF Department of Family, Youth and Community Sciences, February 2016.